Factors that predict brook trout distribution, thermal habitat, and abundance in Northwestern Ontario streams - Picard, Christopher Robert (My University, 1995)
Predictive models were developed to improve the understanding of stream-resident brook trout (Salvelinus fontinalis) populations and habitat in northwestern Ontario, and to facilitate protection of stream-resident brook trout from the adverse impacts of timber harvest. Geology-based models correctly predicted trout presence/absence in 75%-80% of streams studied in 1993. However, correct prediction rates declined to 50%-65% when these models were transferred to independent data collected in 1992 and 1994. Combining data from all years produced models that correctly predicted trout presence/absence in 70%-80% of streams. Univariate geology models were best at predicting trout presence (up to 85% correct predictions). One-third of the trout streams data had maximum summer temperatures >22deg.C , and thus are considered marginal. Using the combined data, models with geology and climate variables explained up to 24% of the variation associated with stream temperatures. Stream temperatures were negatively related to brook trout abundance in the combined data. Stability of stream temperatures accounted for 25% of the variation in trout biomass (kg/ha). These models could be used by fisheries managers to implement current guidelines protecting brook trout habitat from the effects of timber harvest.
Keywords: Brook trout Ontario, Northwestern.